Adrenocorticotropin induces mitogen-activated protein kinase phosphatase 1 in Y1 mouse adrenocortical tumor cells - Bey, Paula (2003)
ACTH signaling pathway includes the action of both protein kinases, mainly cAMP-dependent protein kinase (protein kinase A, PKA), and serine/threonine and tyrosine phosphatases. MAPK phosphatase-1 (MKP-1) is a dual activity protein phosphatase involved in the dephosphorylation of MAPK. To determine whether MKP-1 is a component of ACTH cascade, here we investigate the expression levels of MKP-1 gene in Y1 mouse adrenocortical tumor cells under ACTH stimulation. ACTH transiently increased MKP-1 mRNA and protein levels. MKP-1 mRNA increase occurred at 30 min, peaked at 1 h (6-fold), and returned to basal levels thereafter. The ACTH-mediated mRNA increase was blunted by actinomycin D and enhanced by cycloheximide. A cell permeable cAMP analog, 8-bromo-cAMP, also transiently induced MKP-1 mRNA (4-fold) and the PKA inhibitor N-[2-(p-bromocinnamylamino)ethyl]-5-isoquinolinesulfonamid abolished this effect. In contrast, N-[2-(p-bromocinnamylamino)ethyl]-5-isoquinolinesulfonamid only partially reduced the effect of ACTH, suggesting the participation of PKA-independent mechanisms in the hormone-induced MKP-1 expression. In addition, we show that the rise in intracellular Ca2+ and protein kinase C activation had a potent synergic effect on ACTH- and 8-bromo-cAMP-mediated MKP-1 induction. In summary, our findings demonstrate that MKP-1 is another component of ACTH signaling cascade and indicate that this hormone may potentially down-regulate MAPKs.